Pemberdayaan dan Pendampingan Taman Pendidikan Al-Qur'an (TPQ) Nurul Huda Dalam Pembelajaran Ibadah Amaliah di Kelurahan Gading Kasri Klojen Kota Malang - Awwalliyah, Intan Nurul; Hafikhi, Ahmad Iqbal; Ahsanuddin, Mohammad; Holidi, Iqbal; Safitri, Heida Ifkari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This dedication is motivated by the potential and persistence of children in learning religion, which has not been further sheltered by institutions engaged in the religious field. This is the main reason students do community service by developing the Al-Qur'an Education Park (TPQ) at the Nurul Huda Gading Kasri prayer room, Malang. This service activity aims to increase religious insight in early childhood through several learning methods. This service activity uses the tahsin method, story telling, learning by singing and role playing. Target achievements in empowering and assisting TPQ Nurul Huda through learning religious worship to increase the quality of education and shape the Islamic character of students. So it is hoped that this empowerment and mentoring program can help TPQ Nurul Huda become a legal institution and continue to grow.